2004
DOI: 10.1186/gb-2004-5-6-225
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Eukaryotic genomes are full of long terminal repeat (LTR) retrotransposons. Although most LTR retrotransposons have common structural features and encode similar genes, there is nonetheless considerable diversity in their genomic organization, reflecting the different strategies they use to proliferate within the genomes of their hosts. The electronic version of this article is the complete one and can be found online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(110 citation statements)
references
References 31 publications
2
103
1
1
Order By: Relevance
“…We understand, in agreement with Havecker et al (2004), that genomes of close species can show similar lineages or members of one retrotransposon group, and that possible divergences in their DNA sequences and genomic organization can be found in different species. However, although we were unable to obtain the exact sequence of this element in each species or to determine differences in copy number between the species studied, FISH and dot blot assays did reveal some differences in signal intensity.…”
Section: In Fact This Probe Showed Successful Hybridization In Both supporting
confidence: 67%
See 1 more Smart Citation
“…We understand, in agreement with Havecker et al (2004), that genomes of close species can show similar lineages or members of one retrotransposon group, and that possible divergences in their DNA sequences and genomic organization can be found in different species. However, although we were unable to obtain the exact sequence of this element in each species or to determine differences in copy number between the species studied, FISH and dot blot assays did reveal some differences in signal intensity.…”
Section: In Fact This Probe Showed Successful Hybridization In Both supporting
confidence: 67%
“…Retrotransposons are one of the main representatives of repetitive families, which are amplified and dispersed along the genome using a reverse transcription of an intermediate RNA (Kazazian Jr 2004;Havecker et al 2004). The two major super-families of LTR-retrotransposons are the Ty1-copia-like and Ty3-gypsy-4 like, and they have been related to large expansions and contractions in genome size (Bennetzen et al 2005), reaching large proportions in several plant genomes, such as in Zea mays L. (Schnable et al 2009;Lisch and Bennetzen 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that descendent copies might integrate differentially into their chromosomes-of-origin to create the similarity within chromosomes. However, transcripts of retrotransposons leave the nucleus for reverse transcription prior to integration (Havecker et al 2004). Although some targeting of elements is known for particular chromosomal regions, such as in telomeric repeats (Anzai et al 2001;Xie et al 2001), the local specificity needed to explain our results has never been observed.…”
Section: Violaceumcontrasting
confidence: 47%
“…The movement of a specific DNA fragment takes place when the gag gene (group antigen gene) encodes the protein that forms the virus-like particle inside which reverse transcription. The pol gene encondes enzymatic functions, including the protease that cleaves the Pol polyprotein, a reverse transcriptase that copies the retrotransposon's RNA into cDNA, and an integrase that integrates the cDNA into the genome [16].…”
Section: Retrotransposon Mechanismmentioning
confidence: 99%